Forms of intercultural collaboration between institutions of higher education and indigenous and afro-descendant peoples in Latin America - Mato, Daniel Alejandro (2011)
This article offers an overview of the main forms of intercultural collaboration between institutions of higher education (IHE) and organizations or communities of indigenous and Afro-descendant peoples in Latin America. This overview is based on research done by the Project on Cultural Diversity, Interculturality and Higher Education (the Project) of the UNESCO International Institute for Higher Education in Latin America and the Caribbean, which I have the responsibility of coordinating. Since 2007, the Project has studied some 40 specific experiences oriented to respond to the needs, demands and proposals of communities and/or organizations of indigenous and Afro-descendant peoples, and this has been complemented by the analysis of partial information on some 80 other initiatives.1 The forms of collaboration are context-specific, and therefore varied, including diverse kinds of programs for the inclusion of individuals of those peoples in ‘conventional’ universities, specific curricular programs created by ‘conventional’ IHE, partnerships between IHE and those kinds of organizations, as well as innovative models of IHE created either by those kinds of organizations, state agencies, or the Indigenous Peoples Fund, a peculiar multilateral organization.